Adsorption and dissociation of COCl2 on the rutile TiO2(110) surfaces: a systematic first-principles study. Issue 37 (20th September 2021) - Deng, Pan; Li, Liang; Liu, Dachun; Chen, Xiumin; Jiang, Wenlong
Abstract : The catalytic degradation of highly toxic phosgene (COCl2 ) on rutile TiO2 (110) surface with different degrees of reduction was systematically studied by first principles study. Abstract : The adsorption and dissociation of phosgene (COCl2 ) molecules on three kinds of rutile TiO2 (110) surfaces (stoichiometric: TiO2 -Sto; oxygen defective: TiO2 -Ov; and substoichiometric: TiO1.875 ) were investigated based on density functional theory calculations. The nature of interactions between the COCl2 molecule and rutile TiO2 (110) surfaces with different degrees of reduction was researched by the analysis of geometries, electron density difference, adsorption energies and density of states (DOS). Computational results show that COCl2 indicates instability and will dissociate directly without the presence of transition states on a substoichiometric TiO1.875 (110) surface. The adsorption and dissociation behavior of COCl2 on the rutile surface is not only helpful in providing theoretical support for the clean and efficient degradation of COCl2, but also helpful in elucidating the role of COCl2 as an intermediate product in the carbochlorination of titanium ore.